A comparison of low dose ultrasound and far infra-red therapies in patients with mechanical neck pain - Marwa Mohamed Hany Sedeek Abousenna; Amr Saadeldeen Mohamed Shalaby; Aksh Chahal; Abu Shaphe (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: To compare the effect of low-dose continuous ultrasound and far-infrared interventions for reducing pain in patients with mechanical neck pain. Method: The experimental study was conducted from April 2016 to January 2017 at the electrotherapy laboratory of the Department of Physical Therapy, College of Applied Medical Sciences, Jazan University, Jazan, Saudi Arabia, and comprised female patients diagnosed with mechanical neck pain. They were divided into two equal groups, with Group A receiving 3 sessions per week of low-dose continuous ultrasound on the cervical region for 7 weeks, and Group B receiving far-infrared treatment on the same patterns. Both groups received stretching, strengthening exercises and transcutaneous electrical nerve stimulation. Pain tolerance was assessed at baseline and post-intervention using digital algometer. Data was analysed using SPSS 17. Results: Of the 30 women with a mean age of 21.36±1.14 years, there were 15(50%) in each of the two groups. There was a significant decrease in post-intervention bilateral values compared to baseline in both groups. Group B showed higher significant values than Group A (p<0.05). Conclusions: Far-Infrared was found to be much better than low-dose continuous ultrasound for reducing pain in patients suffering from mechanical neck pain. Key Words: Pain tolerance, Ultrasound, Infrared, Trigger points, Mechanical neck pain, Algometer. Continuous....